Public Theology in Brazil: A First Overview - Sinner, Rudolf von (Toronto journal of theology, 2014)
In view of current challenges in the Brazilian public sphere, discussion on the presence of crucifixes in courthouses in the state of Rio Grande do Sul, as well as on the activities of evangélico congressmen, this article offers a first overview of the reflection on a public theology in Brazil. It presents four lines of thought in the emerging Brazilian discussion, starting in 2001 and getting new energy with the creation of the Global Network of Public Theology in 2007. The first tendency focuses on the academic citizenship of theology, the second seeks to recover a liberal Protestant tradition in contrast to the dominant fundamentalisms, while the third, situated in Latin American left-wing evangelicalism, promotes a dialogue with post-metaphysical and post-secular thinkers, namely Jürgen Habermas. The fourth tendency is being presented more at large, a public theology as theology of citizenship, stemming from Hugo Assmann, incorporating central elements of liberation theology and theological assets from the Lutheran tradition. Finally, the article seeks to show the pertinence and potential of a public theology in Brazil—both with boldness and humility. Underlying is the constant question, what is public theology? The article seeks to answer it, but not with a clear-cut and uniform definition. Rather, it explores opportunities, reviewing concrete challenges and current trends, and tries to argue why a public theology is relevant to and fruitful for the Brazilian context—and probably beyond it.